2021
DOI: 10.3390/cells10030551
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Optical Coherence Tomography Angiography (OCTA) Parameters in a Black Diabetic Population and Correlations with Systemic Diseases

Abstract: This is a cross-sectional, prospective study of a population of black diabetic participants without diabetic retinopathy aimed to investigate optical coherence tomography angiography (OCTA) characteristics and correlations with systemic diseases in this population. These parameters could serve as novel biomarkers for microvascular complications; especially in black populations which are more vulnerable to diabetic microvascular complications. Linear mixed models were used to obtain OCTA mean values ± standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
2
1
0
1
Order By: Relevance
“… 31 , 33 35 For other parameters such as smoking history, we did not find a correlation consistent with previous studies. 31 , 34 , 36 This suggests that our data are in agreement with the literature at large and that our significant findings are those with a higher effect size.…”
Section: Discussionsupporting
confidence: 91%
“… 31 , 33 35 For other parameters such as smoking history, we did not find a correlation consistent with previous studies. 31 , 34 , 36 This suggests that our data are in agreement with the literature at large and that our significant findings are those with a higher effect size.…”
Section: Discussionsupporting
confidence: 91%
“…Only a few studies in the literature correlate systemic parameters with OCT parameters in diabetic patients, and as far as we know, none in children. Shaw et al 58 investigated possible correlations between diabetes complications and OCTA parameters in a black adult population and, similarly to how our study, found that only heart disease had statistical correlations to SCP vessel density, while all other parameters, including proteinuria, were not significantly associated with any OCTA measurement in multi-variate analysis. The authors concluded that OCTA measures may serve as valuable biomarkers of systemic vascular functioning in DM and guide the physician to refer patients for closer monitoring of other systemic diseases.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, these OCTA imaging biomarkers may hold predictive potential for CVD diagnosis and risk in diabetics. One prospective study of Black patients with diabetes found that heart disease, defined as prior diagnosis of heart failure, coronary artery disease, or myocardial infarction, significantly correlated with deep capillary plexus vessel density after multivariate analysis [106]. This provides further evidence in favor of this emerging, though nonspecific, imaging biomarker as reflective of general cardiovascular health.…”
Section: Optical Coherence Tomography Angiographymentioning
confidence: 82%